Direct and indirect barriers to hypothetical access to care among Canadian forces health services personnel - Jennifer Born; Christine Frank (Springer, 2023)
Abstract Background Though research among Canadian Forces Health Services (CFHS) personnel is limited, the literature suggests formal healthcare is underused. Though much research has been conducted on particular barriers (e.g., stigma), examining a breadth of barriers could better inform behavioral interventions. Furthermore, work has yet to examine the indirect effects of barriers through their impact on intentions to access care. Methods CFHS participants were randomly assigned to complete either a mental health (N = 503) or physical health (N = 530) version of the survey. The survey included questions on the perceived impact of barriers, health-related information (e.g., past access to care), intention to seek care, and two hypothetical scenarios (i.e., pneumonia and back injury or post-traumatic stress disorder and depression) as a proxy of access to care. Multiple regressions using Hayes PROCESS macro were conducted to assess the direct and indirect effects (through intentions) of the barriers on hypothetical access to care. Results Results show conflict with career goals barriers were indirectly linked to all health outcomes, and directly linked to mental health outcomes. Treatment preference barriers were directly and indirectly linked to care seeking only for mental health, while resource barriers were directly linked to care seeking only for physical health. Knowledge and ability to access care barriers were directly linked to care seeking for depression and pneumonia. Implications Interventions to improve treatment-seeking should be developed only after the behavioural antecedents are understood, and should focus on combining evidence-based techniques to simultaneously target multiple aspects of the behaviour.